Profiles of physical frailty, social frailty, and cognitive impairment among older adults in rural areas of China: a latent profile analysis - Dong, Qian; Bu, Xiaolong; Wang, Ting; Liu, Man; Zhong, Feng; Liu, Cuiping (Frontiers in Public Health, 2024)
Background: As China rapidly ages, it has now become a deeply aging society with the largest number of older individuals in the world. The issue is particularly severe in rural areas. With the aging population growing and the older population expanding, health problems are becoming more prevalent among older individuals, particularly frailty and cognitive impairments. This study aimed to identify the profiles of physical frailty, social frailty, and cognitive impairment among older adults and explore the influencing factors. Methods: In this cross-sectional study, participants were recruited from six villages in four cities in Shandong Province, China from July to October 2023 through cluster random sampling. Latent profile analysis was used to determine the profiles of physical frailty, social frailty, and cognitive impairment. Chi-square tests and Mann-Whitney U tests were used for univariate analysis, while binary logistic regression was used to analyze the related factors. Results: 769 older adult care in rural areas showed two profiles: the "high cognitive function and low frailty" group (73.7%, n=567) and the "low cognitive function and high frailty" group (26.3%, n=202). A binary logistic regression found that older people were more likely to be aged 80 or older (OR=2.253, p=0.029), have a low income level (OR=1.051, p=0.007), have one or two (OR=2.287, p=0.004), or more than three chronic diseases (OR=3.092, p=0.002), and report moderate (OR=3.406, p=0.024) or poor health status (OR=9.085, p<0.001) in the "low cognitive function and high frailty" group. Meanwhile, older adults who have completed high school (OR=0.428, p=0.005) or junior college and above (OR=0.208, p=0.009), and engage in adequate physical activity (OR=0.319, p<0.001) were more likely to be in the "high cognitive function and low frailty" group. Conclusion: In the future, medical professors should increasingly prioritize promptly identifying and intervening in cognitive decline and frailty status in older individuals without delay.